Relative consumption, relative wealth, and long-run growth: When and why is the standard analysis prone to erroneous conclusions? - Franz X. Hof; Klaus Prettner (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2020)
We employ a novel approach for analyzing the effects of relative consumption and relative wealth preferences on both the decentralized and the socially optimal economic growth rates. In the pertinent literature these effects are usually assessed by examining the dependence of the growth rates on the two parameters of the instantaneous utility function that seem to measure the strength of the relative consumption and the relative wealth motive. We go beyond the sole consideration of parameters by revealing the fundamental factors that ultimately determine long-run growth. In doing so we identify widely used types of status preferences in which the traditional approach is prone to erroneous conclusions. For example, in one of these specifications the parameter that seems to determine the strength of the relative consumption motive actually also affects the strength of the relative wealth motive and the elasticity of intertemporal substitution.
Keywords: D31; D62; O10; O30; 330; relative consumption; relative wealth; quest for status; long-run economicgrowth; social optimality; deep factors